2021
DOI: 10.1080/17452007.2021.1970506
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and coordination of building design: an experience of BIM learning/upskilling

Abstract: The implementation of Building Information Modelling (BIM) in the Architecture, Engineering, Construction and Operations (AECO) industry requires multidisciplinary teams equipped with new technical and managerial skills. Professionals that are inexperienced or unfamiliar with the BIM design process face difficulties in transposing complex concepts into BIM modelling and coordination practices, despite governments, industry bodies, and academia's efforts. With this issue in mind, this article's objective is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The results obtained corroborate what other authors have detected. For BIM to be properly applied, it requires a collaborative work environment (Presente de Souza et al ., 2021). To foster the collaborative environment, the importance of communication between team members is highlighted as it generates success in the development of construction projects (Setiawan et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained corroborate what other authors have detected. For BIM to be properly applied, it requires a collaborative work environment (Presente de Souza et al ., 2021). To foster the collaborative environment, the importance of communication between team members is highlighted as it generates success in the development of construction projects (Setiawan et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Culture has been considered an essential element in BIM practice (Alankarage et al, 2023). A BIM work environment requires a collaborative work environment consistent with AEC practices (Presente de Souza et al, 2021). Research has shown that the lack of encouragement of team collaboration functions as a barrier in the use of BIM, so there is a need to investigate the culture of team collaboration among stakeholders, including clients, in the planning, Effective communication in BIM design and construction phases (Kapogiannis and Sherratt, 2018;Piroozfar et al, 2019).…”
Section: Collaborative Culturementioning
confidence: 99%
See 1 more Smart Citation
“…BIM has proved to be an effective tool for architectural design [6,7]; design-related analysis, such as energy saving [8], solar radiation and reduction [9], daylighting and illumination [10], acoustics [11], and orientation [12]; construction monitoring and management [13]; procurement [14]; project management [15]; facility management [16,17]; coordination between building service systems of mechanical, electrical and plumbing (MEP) models [18]; working/detail drawings [19,20]; and bills of quantities (BoQs) [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A superação dessas dificuldades envolve um esforço conjunto da indústria, seja por meio da atualização de currículos para treinamento e capacitação dos profissionais para modelagem e colaboração (DE SOUZA et al, 2021); da elaboração de bibliotecas e famílias de componentes, templates de projeto e protocolos e padrões para colaboração (ORAEE et al, 2019;SACKS et al, 2018;SOLIHIN, EASTMAN, LEE, 2016) entre escritórios e construtoras; e da ampliação de políticas e normas (ORAEE et al, 2019) para a efetiva adoção do BIM nas fases de projeto e obra.…”
Section: Considerações Finaisunclassified